Showcasing Emptiness? Voicing Redemption Through ‘Saharomania’ in the French Literary Imaginary - Amina Zarzi (Cahiers Victoriens et Edouardiens)
The Napoleonic campaigns paved the way for French metropolitan travellers, military officers and literary authors to roam the barren stretches of North African deserts. Initially, imperial expansion was what brought French explorers to these lands. As devoted adventurers, they were quick to predict the literary opportunities of showcasing emptiness in military, scientific and literary projections. At once empty and loaded with spiritual charge, the desert embodies the essence of mystical connotations, for those who master decrypting its unsettling silence. This article argues that this seemingly empty space is in fact the cradle of spiritual pursuits, deployed in Sèbe’s ‘Saharomania’ concept as a redemptive locus. Showcasing emptiness thus represented a challenge to the spread of the cult of Western materialism. This is illustrated in two ways: the vision of French authors (Saint-Exupéry, Ernest Psichari, Charles de Foucauld, and Eric-Emmanuel Schmitt) who, taken together, amount to the establishment of a French desert genealogy of ‘Saharomania’, and the ways in which it offers a different reading of the accompanying Orientalist understanding of such works, through the prism of the redemptive wisdom of the desert. While taking part in Said’s Western canon on the Orient, redemptive ‘Saharomania’ also participates in the wider definition of the ways in which the imaginary of emptiness fuelled the fin-de-siècle cult of the void. It is in light of the alterity of the desert that the concept of ‘Saharomania’, specific to France, can be read: because showcasing emptiness meant empowerment, the success of the inscription of bareness in the imaginary of the French metropolitan public, and also its literary inheritance, was necessary to celebrate the French national sentiment. Taking the demanding crossing of the desert to heart, often for nationalist pursuits, was necessary to triumph over the physically and mentally exhausting desert. However, this article argues, authors incline when faced with the grandeur of the Sahara Desert, and its emblematic nomad dwellers, amidst the journey of the conventional fate of loss in the sands, ultimately changing the initial motives of the crossing. Thus, rather than condemning the present French literary productions within the confines of the orientalist and exotic tropes, this article offers different but no less significant interrogations about how ‘Saharomania’ valorises the desert as a locus of the higher forms of humankind, particularly defying the cult of Western hollowness through articulating spiritual resonance in the realm of the void.